Epidemiology of Severity of Temporomandibular Disorders in Brazilian Women - Duarte Bonini Campos, Juliana Alvares [UNESP]; Carrascosa, Andrea Correa [UNESP]; Sampaio Bonafe, Fernanda Salloume [UNESP]; Maroco, Joao (Quintessence Publishing Co Inc, 2014)
Aims: To evaluate the severity of temporomandibular disorders (TMD) of women in the municipality of Araraquara (Brazil) as well as the contribution of the perception of oral health, mandibular functional limitation, and sociodemographic variables on the severity of TMD. Methods: The participants were interviewed by telephone. Information regarding age, marital status, economic level, education, and use and type of dental prostheses was surveyed. To evaluate TMD severity, mandibular functional limitation and perception of oral health, Fonseca's Anamnesic Index (IAF), the Mandibular Function Impairment Questionnaire (MFIQ), and the General Oral Health Assessment Index (GOHAI) were used. To evaluate the contribution of these variables on TMD severity, a structural equation model (SEM) was fitted to the data and assessed by usual goodness-of-fit indices. Results: A total of 701 women with a mean age of 44.36 years (SD = 16.31) participated. According to the IAF, 59.6% (95% confidence interval = 56.00%-63.2%) of the women were classified as having TMD, of which 63.9% presented light, 26.8% moderate, and 9.3% severe TMD. Mandibular functional limitation was low in 91.0% of the women, moderate in 7.1%, and severe in 1.9%. Goodness-of-fit for the structural model was adequate. The predictors explained 43% of the variation in the TMD severity, with significant contributions of the variables dental prostheses (beta = -.008; P = .006), perception of oral health (beta = -.43; P < .001), and mandibular functional limitation (beta = .014; P = 014). Conclusion: The severity of TMD among Brazilian women was greater in non-users of dental prostheses and was also associated with greater mandibular functional limitation and poor perception of oral health.
Keywords: oral health; scales; structural equation modeling; temporomandibular disorders (TMD); women